S24 A self-management programme of activity, coping and education (SPACE) for COPD: A randomised non-inferiority trial in a pulmonary rehabilitation population. (14th November 2013) - Horton, E; Mitchell, K; Johnson-Warrington, V; Apps, L; Young, H; Singh, S; Singh, S
Abstract : Introduction: Self-managed programmes for patients with COPD offer an alternative to conventional pulmonary rehabilitation (PR). Previously reported self management (SM) programmes either offer short education sessions or action plans or are long intensive programme with a high level of support which are more comprehensive than tradition UK PR programmes. There is limited data reported on self managed approaches to PR which offer minimal support for education, skills acquisition and exercise in comparison to PR in the UK. We have recently developed a SM programme for patients with COPD (SPACE for COPD) and have completed studies in primary care 1 . The demand for PR is high but the service is compromised by limited access and drop out rates. Therefore the aim of this study was to determine if SPACE for COPD is noninferior to (as good as) PR for patients with COPD over 7 weeks. Methods: 287 patients (187 male: mean (SD) age 67 (9) yrs; FEV1 1.25 (0.55); BMI 27.63 (6.22) kg/m 2 ) with COPD were consented and randomised to either SPACE for COPD or PR. Those who were assigned to the SPACE for COPD group received an introduction to the SPACE for COPD manual and 2 telephone calls at 2 and 4 weeks. Those assigned to PR received 14, 2 hour sessions of education and exercise over 7 weeks. The primary outcome was the Chronic Respiratory Questionnaire (CRQ) dyspnoea, with secondary measure of CRQ fatigue, emotion and mastery, Incremental Shuttle Walk Test (ISWT) and Endurance Shuttle Walk Test (ESWT). Measures were taken at baseline and 7 weeks. Within and between group differences were analysed using paired and unpaired t-tests respectively. Results: Please see table 1 . Conclusion: SPACE for COPD can improve dyspnoea and endurance capacity over 7 weeks to a similar level to PR, although it remains unclear to its noniferiority to PR. The SPACE for COPD programme does offer a number of health benefits despite it involving limited support and could offer a suitable alternative to patients with COPD who would otherwise not attend conventional rehabilitation. References: Mitchell-Wagg K et al . (2012). Thorax 67 (Suppl_2) A25–26.